Potential of phosphate solubilizing fungi isolated from peat soils as inoculant biofertilizer - Deni Elfiati; Delvian DELVIAN; Hamidah Hanum; Arida Susilowati; Henti Hendalastuti Rachmat (Society for Indonesian Biodiversity, 2021)
Abstract. Elfiati D, Delvian, Hanum H, Susilowati A, Rachmat HH. 2021. Potential of phosphate solubilizing fungi isolated from peat soils as inoculant biofertilizer. Biodiversitas 22: 3042-3048. Phosphate-solubilizing fungi are the microbes that have the ability to dissolve insoluble phosphate and made it available for plants. Therefore, the purpose of this study was to obtain the phosphate-solubilizing fungi from peat soils. Peat soil samples were taken in a composite at a depth 0-20 cm from the peat ecosystem in Nagasaribu Village, Lintong Nihuta Sub-district, Humbang Hasundutan District, North Sumatra, Indonesia. Soil samples were isolated to obtain phosphate-solubilizing fungi using the Pikovskaya selective medium. The obtained isolates were tested for their ability to dissolve phosphate qualitatively by calculating the dissolution index values and quantitatively by calculating the available phosphorus on Pikovskaya medium by using four phosphate sources, namely Ca3(PO4)2, AlPO4, FePO4, and phosphate rock. Total of 12 isolates of phosphate-solubilizing fungi was obtained during the present study. Based on the results of qualitative and quantitative testing, all 12 isolates have the ability to release phosphate from the four tasted phosphate sources. The qualitative test obtains dissolution index values that vary from 2.55 to 4.25, while quantitatively, the isolates were able to dissolve phosphate in the value range from 17.77 ppm to 69.86 ppm. The top five fungal isolates with highest phosphate-solubilizing potential were FG5, FG8, FG9, FG11, and FG12. Based on molecular identification, these five isolates were identified as Aspergillus niger.